2014
DOI: 10.1167/iovs.13-13062
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology and Optical Coherence Tomography to Evaluate Parkinson Disease Severity

Abstract: Patients with greater damage in the RNFL tend to have lower QOL and more severe PD symptoms. Foveal thicknesses and the PERG N95 component provide good biomarkers for predicting QOL and disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 47 publications
6
92
1
2
Order By: Relevance
“…44 Many parts of the visual system have been implicated as the cause for visual deficits, such as the retina, where thinning of the inner retinal nerve fiber layer and decreased dopamine concentration seem to mirror the loss of dopaminergic neurons in the basal ganglia. 2,45,46 Pattern electroretinogram studies in PD subjects have shown significant loss at midspatial frequencies of 4 cyc/deg, corroborating our findings. 47 With the addition of motion, both PD and control subjects improved their contrast sensitivity at low spatial frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…44 Many parts of the visual system have been implicated as the cause for visual deficits, such as the retina, where thinning of the inner retinal nerve fiber layer and decreased dopamine concentration seem to mirror the loss of dopaminergic neurons in the basal ganglia. 2,45,46 Pattern electroretinogram studies in PD subjects have shown significant loss at midspatial frequencies of 4 cyc/deg, corroborating our findings. 47 With the addition of motion, both PD and control subjects improved their contrast sensitivity at low spatial frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…In this context, optical coherence tomography (OCT), a non-invasive imaging technique, provides reproducible, high-resolution cross-sectional imaging of the retinal nerve fiber layer (RNFL) and optic nerve head topography, providing an objective tool to diagnose axonal damage and thus constituting a "window into the brain" (London et al, 2013). A significant reduction in peripapillary RNFL thickness has been reported in patients with various neurological disorders such as multiple sclerosis (Sergott et al, 2007;Thrower, 2007), Alzheimer's disease (Parisi et al, 2001;Berisha et al, 2007;Marziani et al, 2013;Larrosa et al, 2014;Ascaso et al, 2014) or Parkinson's disease (Inzelberg et al, 2004;Hajee et al, 2009;Garcia-Martin et al, 2014;Jimenez et al, 2014), suggesting that this technique may also prove to be useful in other neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous OCT studies are inconclusive. Some studies revealed RNFL thinning in PD cases [13][14][15][16], while other does not support this [17][18][19][20]. The reason of result discrepancies may be qualification of PD patients with glaucoma to the analysis, which has proven influence on RNFL thickness.…”
Section: Discussionmentioning
confidence: 99%